E-Commerce Sales System Based Mobile Android (Case Study: PT.Makmur Cipta Sejahtera) - Agung Kurniawan Toing; Ardie Halim Wijaya (Tech-E, 2019)
With the passage of the sales process manually which is less efficient and less effective in PT. Makmur Cipta Sejahtera, it needs a program to support the efficiency and effectiveness of the sales process. The process of ordering goods that still use manual methods to use mail order goods, make the authors design and create an Android-based sales program. This program will be addressed to PT. Makmur Cipta Sejahtera entitled "E-COMMERCE SALES SYSTEM BASED MOBILE ANDROID (CASE STUDY: PT. MAKMUR CIPTA SEJAHTERA)". The research method is done by two methods: analysis of research and data collection methods. Methods of data collection by interview, observation and literature. User needs, among others are able to provide accurate reports, user-friendly and simple interface, capable of showing product details, and how to use that are not complicated. After the design, manufacture, and testing of the program, some conclusions that this program may support the efficiency and effectiveness of the sales process, minimize the opportunities for error, and cost efficiency in terms of paperless. Hopefully this program can be a learning for students who want to take thesis with the title associated with the sale of e-commerce system based on mobile android. I welcome any comments and suggestions for the design of the system is still flawed. then a number of conclusions that this program may support the efficiency and effectiveness of the sales process, to minimize opportunities for error, and cost efficiency in terms of paperless. Hopefully this program can be a learning for students who want to take thesis with the title associated with the sale of e-commerce system based on mobile android. I welcome any comments and suggestions for the design of the system because it still flawed.